2004
DOI: 10.1111/j.1432-1033.2004.04319.x
|View full text |Cite
|
Sign up to set email alerts
|

Structured DNA promotes phosphorylation of p53 by DNA‐dependent protein kinase at serine 9 and threonine 18

Abstract: Phosphorylation at multiple sites within the N-terminus of p53 promotes its dissociation from hdm2/mdm2 and stimulates its transcriptional regulatory potential. The large phosphoinositide 3-kinase-like kinases ataxia telangiectasia mutated gene product and the ataxia telangectasia and RAD-3-related kinase promote phosphorylation of human p53 at Ser15 and Ser20, and are required for the activation of p53 following DNA damage. DNA-dependent protein kinase (DNA-PK) is another large phosphoinositide 3-kinaselike k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…We compared post-translational modification of p53 in Hmgb1 ϩ/ϩ and Hmgb1 Ϫ/Ϫ cells in response to genotoxic stress caused by treatment with MP, araC, and FU. To monitor the status of p53, we used antibodies to phosphorylated forms of p53 (Soubeyrand et al, 2004). Ser9 and Ser15 in human p53 are evolutionarily conserved residues, corresponding to Ser12 and Ser18 in murine p53; these residues can be phosphorylated by several protein kinases including ATM, ATR, and DNA-PK (Chao et al, 2003).…”
Section: Hmgb1 Modulated Phosphorylation Of P53 and H2ax Proteins Aftmentioning
confidence: 99%
“…We compared post-translational modification of p53 in Hmgb1 ϩ/ϩ and Hmgb1 Ϫ/Ϫ cells in response to genotoxic stress caused by treatment with MP, araC, and FU. To monitor the status of p53, we used antibodies to phosphorylated forms of p53 (Soubeyrand et al, 2004). Ser9 and Ser15 in human p53 are evolutionarily conserved residues, corresponding to Ser12 and Ser18 in murine p53; these residues can be phosphorylated by several protein kinases including ATM, ATR, and DNA-PK (Chao et al, 2003).…”
Section: Hmgb1 Modulated Phosphorylation Of P53 and H2ax Proteins Aftmentioning
confidence: 99%
“…Thr18 phosphorylation is considered the more critical of the two, as it directly attenuates its interaction with Mdm2 (Craig et al, 1999;Lai et al, 2000;Sakaguchi et al, 2000;Schon et al, 2002). Thr18 is phosphorylated by several kinases including VRK1, Chk1, Chk2, DNA-PK (Soubeyrand et al, 2004) and casein kinase 1 (CK1) (Dumaz et al, 1999;Sakaguchi et al, 2000). However, as these findings were based on in vitro assays, the conditions under which Thr18 phosphorylation occurs, in cultured cells, have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Human p53 is rapidly phosphorylated at Ser9 after exposure to c-rays and to UV light. Several kinases, such as casein kinase 1d (CK1d), CK1e, and DNA-PK have the ability to phosphorylate p53 at Ser9, in addition to several other serine residues, but the detailed role of phospho-p53 (Ser9) is not clear [11]. Recently, Cordenonsi et al reported that human p53, phosphorylated at Ser9, and injected into Xenopus embryos, serves as an activator of mesoderm marker genes and that phospho-p53 (Ser9) promotes TGF-b cytostasis in human cells [12].…”
Section: Introductionmentioning
confidence: 99%